Coding learning model in speaking courses as an innovation to improve 21st century skills - Eliya, Ixsir (JOALL (Journal of Applied Linguistics and Literature), 2024)
Integrating coding into learning is one of the opportunities afforded by technology in education. However, the use of coding in tertiary institutions is still underutilized in the field of language learning. The purpose of this research is to develop a coding learning model for the speaking course that suits the needs of lecturers and students in the teaching and learning process. This research involves Research and Development using the ADDIE model. The subjects in this study consisted of three lecturers and seventy-eight students from five universities in Bengkulu Province, as well as three experts in the fields of materials, media, and language. The results of the study reveal that this model has three main activities: pre-learning, learning, and post-learning, which have five main phases: perception, exploration, collaboration, coding, and publication. The validation test results obtained ‘very good’ qualifications from material experts and were appropriated by linguists and media experts. The validation results indicate that this model is considered feasible to use so that it meets the standardization of product development testing.